Host microbiota dictates the proinflammatory impact of LPS in the murine liver. (September 2020) - Suriguga, Su; Luangmonkong, Theerut; Mutsaers, Henricus A.M.; Groothuis, Geny M.M.; Olinga, Peter
Abstract: Gut microbiota can impact liver disease development via the gut-liver axis. Liver inflammation is a shared pathological event in various liver diseases and gut microbiota might influence this pathological process. In this study, we studied the influence of gut microbiota on the inflammatory response of the liver to lipopolysaccharide (LPS). The inflammatory response to LPS (1–10 μg/ml) of livers of specific-pathogen-free (SPF) or germ-free (GF) mice was evaluated ex vivo, using precision-cut liver slices (PCLS). LPS induced a more pronounced inflammatory response in GF PCLS than in SPF PCLS. Baseline TNF-α gene expression was significantly higher in GF slices as compared to SPF slices. LPS treatment induced TNF-α, IL-1β, IL-6 and iNOS expression in both SPF and GF PCLS, but the increase was more intense in GF slices. The anti-inflammatory markers SOCS3 and IRAK-M gene expression was significantly higher in GF PCLS than SPF PCLS at 24h with 1 µg/ml LPS treatment, and IL-10 was not differently expressed in GF PCLS than SPF PCLS . In addition, TLR-4 mRNA, but not protein, at basal level was higher in GF slices than in SPF slices. Taken together, this study shows that, in mice, the host microbiota attenuates the pro-inflammatory impact of LPS in the liver, indicating a positive role of the gut microbiota on the immune homeostasis of the liver. Highlights: Host microbiota mitigates the inflammatory response to LPS in the liver. Divergent response to LPS between specific-pathogen-free and germ-free mice livers. Precision-cut liver slices- model for inflammation of hepatic resident cells.